The Use of New Halal Labeling for Snack Food Production (The Chips by Zkiyah) in Banda Aceh - Amira Dalia; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Written in Halal labeling is a label that informs consumers that the product is halal and the ingredients it contains do not contain prohibited elements so that the product can be consumed by consumers. Product packaging that contains a halal label makes it easier for consumers to identify a product that is halal. So, the aim of this research is to determine the use of new halal labeling in the production of The Chips by Zakiyah snack food in Banda Aceh. This research uses qualitative methods, and then the researcher carries out open interview techniques with research subjects and observations. The research results showed that consumers prefer products that use halal labels. And products that do not use the halal label have a big impact on consumers; besides that, consumers feel satisfied when they buy products that use the halal label. In conclusion, The Chips by Zakiyah is in the process of using the new halal labeling. And for consumers, the new halal label has no effect on purchasing the product.